Independence Square : Arkady Renko in Ukraine - Smith, Martin Cruz, 1942- (Smith, Martin Cruz, 1942- Arkady Renko novels, 2023)
It's June 2021, and Arkady knows that Russia is preparing to invade and subsequently annex Ukraine as it did Crimea in 2014. He is, however, preoccupied with other grievances. His longtime lover, Tatiana Petrovna, has deserted him for her work as an investigative reporter. His corrupt boss has relegated him to a desk job. And he is having trouble with his dexterity and balance. A visit to his doctor reveals that these are symptoms for Parkinson's Disease. This is an ingenious autobiographical conceit, as Martin Cruz Smith has Parkinson's, and is able through Arkady to movingly describe his own experience with the disease. Parkinson's hasn't stopped Smith from his work, and neither does it stop Arkady. Rather than dwell on his diagnosis, he throws himself into another case. An acquaintance has asked him to find his daughter, Karina, an anti-Putin activist who has disappeared. In the course of the investigation, Arkady falls for Karina's roommate, Elena, a Tatar from Ukraine. The search leads them to Kyiv, where rumblings of an armed conflict grow louder. Later, in Crimea, Tatiana reemerges to complicate Arkady's new romance. And as he gets closer to locating Karina, Arkady discovers something that threatens his life as well as the lives of both Elena and Tatiana.